If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -3) + 5x = -4 Reorder the terms: 4(-3 + x) + 5x = -4 (-3 * 4 + x * 4) + 5x = -4 (-12 + 4x) + 5x = -4 Combine like terms: 4x + 5x = 9x -12 + 9x = -4 Solving -12 + 9x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 9x = -4 + 12 Combine like terms: -12 + 12 = 0 0 + 9x = -4 + 12 9x = -4 + 12 Combine like terms: -4 + 12 = 8 9x = 8 Divide each side by '9'. x = 0.8888888889 Simplifying x = 0.8888888889
| 6/y=1 | | 6=5x+10 | | 5-3s=7s+2 | | 7(1-6c)= | | 2w+4v+6z=2 | | 120=4x+40 | | 8x+14-7x=-3-10 | | 5x+10-2x=-8 | | 1-(25/x^2)=0 | | 5x-2x+10=-8 | | 67+21/28 | | 3=7x-10 | | 2x^4-30=2 | | -5(4-3y)= | | 81y=16(5y+3) | | 67+21/2*20 | | -0.2(3.25-6x)=1.9x | | 48=3t-11t | | 50n=2000+40n | | 5x+10-2x=8 | | X+2x+5x=30 | | 5(x+7)=(5x+35) | | 2x+8+3x=33 | | 8x+3y=76 | | 16-12=x | | 4x+6=-32 | | -2y+3=0 | | 20+x= | | 18-11/4x=7 | | 3y+5=20-2y | | f=epd | | abs(6x+8)=7 |